Moral decision making in international sales negotiations - Zarkada, Anna K.; Fraser, Campbell (My University, 2001)
International sales negotiations are fast becoming a major part of the marketeer's mandate in an increasingly globalised economy. To be successful in that role, managers need to be aware of the limits of acceptability of their behaviours, able to anticipate their counterparts actions and understand the motivations behind them. Presents a cross-national study of 332 experienced sales negotiators' perceptions in Australia, the USA, the UK, Japan, Russia and Greece. It explores the degree to which different tactics are considered morally acceptable in each country and how the decision-making frameworks the managers employ affect their evaluation. The results demonstrate that, although moral acceptability of specific practices, the overall level of tolerance and the effect of each one of a set of decision-making variables vary among different nationalities, the mechanism of the evaluation can be analysed by a single explanatory-model.
Keywords: Decision making; Ethics; International marketing; National cultures